Expressing freedom and taking liberties: the paradoxes of aberrant science. Issue 1 (26th May 2006) - Little, M
Abstract : Complete freedom does not exist, despite people's preparedness to die for it. Scientific freedom is much defended and yet much misunderstood. Scientists have limits imposed on their freedom by the disciplines and discourse communities in which they place themselves. Freedom within these socially constructed constraints needs to be distinguished from taking liberties with the rules and practices that make up these constraints, and validate the activities of special groups within society. Scientists (and the public) perceive taking liberties with science's rules and practices as aberrant science, and they often react punitively. Aberrant science can be broadly examined under four headings: wicked science, naughty science, dysfunctional science, and ideologically unacceptable science. When we examine examples of perceived aberrant science, we find that these categories of "misconduct" are connected and often confused. Scientific freedom needs to be redefined with due regard to current understandings of scientists as human beings facing powerful social pressures to deliver results of a particular kind.